Systematic Review of Screen Time Impact on Adolescent Learning and Mental Health - Naing, Khin Sabai (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Technology integration has become crucial to education in the post-COVID era, offering new learning opportunities but also raising concerns about the effects of excessive screen time on adolescents. This study investigates the effects of screen use on academic performance and mental health, focusing on gender differences. Guided by the 2020 PRISMA framework, a systematic review synthesizes recent empirical studies on screen time, academic outcomes, and psychological well-being. Findings indicate complex screen time’s effects: moderate use can support learning and social connection, but excessive use (four to seven hours daily) is consistently linked to depression, anxiety, attention problems, cognitive decline, and problematic social media behaviors. Impacts vary depending on the purpose of use, pre-existing mental health conditions, and social context. Educational technology functions as both a facilitator and a barrier, depending on implementation. Gender patterns are evident, with girls showing more declines in mental health and life satisfaction during early adolescence, while boys face notable but often underrecognized emotional and physical risks. This review highlights the dual nature of digital engagement and underscores the need for balanced, intentional technology use. The results carry practical implications for students, parents, and educators seeking to promote well-being and academic achievement while mitigating risks of excessive screen time.